Self‐generating Brillouin fiber laser using highly nonlinear hafnium bismuth erbium‐doped fiber - Ahmad, Aminah; Cheng, Xiau San; Paul, Mukul Chandran; Dhar, Anirban; Das, Shyamal; Ahmad, Harith; Harun, Sulaiman Wadi (John Wiley & Sons, 2019)
A compact Brillouin fiber laser (BFL) utilizing a newly developed hafnium bismuth erbium-doped fiber (HB-EDF), which functions as both the Brillouin and linear gain media, is realized in the absence of Brillouin pump. It is achieved by the self-Brillouin generation from a 0.2 m length of HB-EDF with high nonlinearity in a laser cavity. The self-generating BFL was obtained in both ring and linear laser cavities. Compared to the ring cavity, the BFL in the linear cavity produced more Brillouin stokes at a lower pump threshold. In the experiment, an eight-line comb with average spacing of 0.087 nm was generated at the HB-EDF pump power of 75.27 mW. This compact BFL has total cavity length of less than 0.5 m, and thus, this is the shortest gain medium reported for Brillouin erbium fiber laser generation without using any Brillouin pump. © 2019 Wiley Periodicals, Inc.